All Iron Battery 3.0 - Dipak Koirala; Surendra K. Gautam; I. Francis Cheng; Peter B. Allen (HardwareX)
Battery storage technology can address a key limitation to renewable energy. Renewable electricity generation (solar and wind) is intermittent. An inexpensive energy storage device with excellent rechargeability and safety is critical for grid applications and for the global transition to renewable energy. In this work, we introduce an energy storage secondary battery based on an aqueous all-iron chemistry with redox mediators. The cell employs commodity chemicals methyl viologen and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) at the anode and cathode, respectively. The result is a highly rechargeable, low-cost energy storage system with a good price-performance ratio compared to commercial rechargeable batteries that is stable for 100+ cycles with 84 % capacity retention. The cell has a volumetric capacity of 9.6 Ah/L (energy of 11.52 wh/L) and power density of 72 Watts/m2.